Georges Sorel and the Naissance of the Fascist Political Myth - Wielomski, Adam (International Studies. Interdisciplinary Political and Cultural Journal, 2022)
Georges Sorel is a Franco-Italian thinker, famous as the creator of the theory of modern political mythology. In Poland Sorel is seen only as a Marxist thinker. In reality, Sorel was a nonorthodox Marxist, but in the last decades of his life he constructed a political mythology of revolution from the Left and the Right. Sorel can be seen in collaboration with communists and sindicalists in Italy and nationalists and monarchists in France. His mixture of communist and nationalist ideas is the ground for the fascist movement of Benito Mussolini.